2011
DOI: 10.1136/bmjopen-2011-000391
|View full text |Cite
|
Sign up to set email alerts
|

Clinical decision making in spinal fusion for chronic low back pain. Results of a nationwide survey among spine surgeons

Abstract: ObjectivesTo assess the use of prognostic patient factors and predictive tests in clinical decision making for spinal fusion in patients with chronic low back pain.Design and settingNationwide survey among spine surgeons in the Netherlands.ParticipantsSurgeon members of the Dutch Spine Society were questioned on their surgical treatment strategy for chronic low back pain.Primary and secondary outcome measuresThe surgeons' opinion on the use of prognostic patient factors and predictive tests for patient selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 43 publications
(36 reference statements)
0
27
0
Order By: Relevance
“…Furthermore, frequency of spinal fusion depends on physician's enthusiasm 77) . Many trials have been made to identify the prognostic patient factors and predictive tests for patient selection, but there is no consensus [78][79][80] . Evidence does not support the use of current tests for patient selection 81) .…”
Section: Fusionmentioning
confidence: 99%
“…Furthermore, frequency of spinal fusion depends on physician's enthusiasm 77) . Many trials have been made to identify the prognostic patient factors and predictive tests for patient selection, but there is no consensus [78][79][80] . Evidence does not support the use of current tests for patient selection 81) .…”
Section: Fusionmentioning
confidence: 99%
“…Similar studies using patient referral data are lacking, but Willems et al evaluated the opinion of 62 Dutch spine surgeons on the use of patient-reported factors (e.g., age, BMI) and predictive tests (e.g., magnetic resonance imaging) in clinical decision-making for spinal fusion [6]. That study showed a lack of professional consensus and indicated that patientreported factors were not consistently incorporated in the surgeons' treatment strategy [6].…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…Improved insight into the current spine surgery decisionmaking process for CLBP patients may clarify some of the aforementioned variations in spinal surgery rates [4], and may ultimately support spine surgery decision-making guidelines [6,11]. Amongst others, it would be insightful to know which CLBP patients are typically referred to spinal surgery, whether patient-reported factors can be identified that are predictive of spinal surgery referral, and if so, to what extent spinal surgery referral is explained by these factors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations